Digital Piety and the Transformation of Political Activism of Youth Hijrah Movement - Ali Ja'far (IAIN Ponorogo, 2020)
Abstract: This paper explains about hijrah, a popular term among urban youths; it refers not only religious, but also political transformation. This activity has been growing massively in the urban area through the internet and in the short after the fall of Soeharto regime where democracy and the technology has become more developed. Digitally, hijrah shapes the narration of being pious, religious and modern-fashionable look. Taking the data from field observation on the hijrah event and following the digital media, this paper attempts to investigate the historical root of hijrah and how the youth utilize modern technology to visualize and share their narration on being politically pious. Borrowing the idea from Birgit Meyer and Bayat about visualization and post-Islamism, this paper has found that although hijrah narration is close to fundamental religious activism and politically promotes Islamic political system, but the agenda has not succeeded. However, hijrah activity is successful in engaging youth through the events such as; sharing session, gathering, book review, festival and preaching which are specifically designed for youths.الملخص: يتناول هذا البحث عن الهجرة وهي مصطلح شائع بين شباب الحضر. ولا يشير هذا الموضوع الى التغير الديني ، بل حتى التغير السياسي. وازدهرت أنشطة الهجرة بعد سقوط سوهارتو بسرعة فائقة وكذلك الديموقراطية والتكنولوجيا . وكونت الهجرة في العالم الرقمي التقوى والدين والحداثة ايضا . آخذا المعلومات من المنهج الميداني مع تتبع الوسائل الهجرة الرقمية، تحاول هذا البحث التحقق عن جذور التاريخ وكيفية تعامل الشباب مع التكنولوجيا المعاصرة لتصور المسائل ونشر الروايات حول موضوع الصالح . نستعير فكر بيرجير ماير وبيات حول التصورية وما بعد الاسلامية ، تكشف هذا البحث موضوع الهجرة قريبة الى جذروية الدينية و من سياسيتها الى السياسية الشرعية ولكن لا تسير هذه الانشطة على ما يرام. ومن نا حية أخرى ، تربط انشطة الهجرة مع الشباب كالمناقشات والمحاضرات ومراجعة الكتب والتجمعات ترابطا وطيدا وناجحا لأنها خصصت مصممة للشبابAbstrak: Tulisan ini menjelaskan tentang hijrah. Sebuah terma yang popular di kalangan anak muda urban. Terma ini tidak hanya merujuk pada istilah akan perubahan keagamaan, tetapi juga perubahan politik. Aktifitas hijrah tumbuh pesat setelah runtuhnya regime Soeharto dimana demokrasi dan perkembangan teknologi semakin maju. Hijrah dalam dunia digital juga membentuk narasi akan kesalehan, keagamaan, dan modernitas. Penelitian ini mengambil data dari observasi lapangan serta mengikuti media digital hijrah. Tulisan ini berusaha menginvestigasi akar sejarah dari hijrah dan bagaimana anak-anak muda menggunakan teknologi modern untuk memvisualisasikan dan menyebarkan narasi tentang kesalihan. Meminjam ide dari Birgit Meyer dan Bayat tentang visualisasi dan post-Islamism, tulisan ini mengungkap bahwa meskipun narasi hijrah itu sangat dekat dengan fundamentalisme agama dan secara politis mendukung sistem politik berlandaskan Islam akan tetapi agenda ini tidak berjalan dengan baik. Sebaliknya, aktifitas hijrah yang mengikat anak muda melalui berbagai event seperti, sesi diskusi, gathering, bedah buku, festival, dan ceramah keagamaan telah sukses mengikat anak muda karena aktifitas itu secara khusus didesain untuk anak muda)